Postoperative management of anaesthesia-associated hypothermia with a forced-air convective warming device. - Jackson, Stephanie Ana Maria. (My University, 1997)
This study investigated the postoperative management of hypothermia of intraoperative origin using a forced-air convective warming device. Hypothermia develops during the intraoperative period partly as a result of disordered thermoregulation induced by anaesthesia and partly because of the nature of the operational injury and the surgical environment. Both the hypothermic state and the consequences of physiological attempts to return the core temperature to normal, which take place during the postoperative period, are associated with non-beneficial effects. Attempts to prevent intraoperative decline in core temperature are a part of anaesthesia management. However, most of the traditional options available are inefficient or ineffective, particularly in adults. This study evaluated the performance of a new device, the forced-air convective warmer, in the management of the postoperative hypothermic state. Results showed that when compared to a hypothermic control group the device made a significant difference to the thermal state of a group of hypothermic postoperative patients but only if it was used for at least two hours postoperation.
Submitted in partial fulfilment of the requirements tor the degree of Master of Medicine (Anaesthesia) in the Department of Anaesthesla University of the Witwatersrand
Keywords: Hypothermia.; Postoperative Complications.